(untitled) (Physical Education, Health and Social Sciences, 2025)
Belt and Road Initiative (BRI), initiated by China, is a revolutionary economic configuration in the world, and China-Pakistan Economic Corridor (CPEC) is a major project in this plan. Although CPEC is a prospective development in terms of developing infrastructure and as an exclusive economy to Pakistan, this initiative comes along with complicated legal issues like protecting investments, right to regulation and adherence to environment and human right requirements. In this paper we will critically analyze Pakistani legal regime of foreign investment in light of CPEC including striking balance between investor protection and the ability of the state to regulate in the interest of the people. Based on the assessment of local legislation, bilateral agreements, and the frameworks of the international law, the paper identifies the loopholes and insecurities of the Pakistani legal framework that can threaten the domestic autonomy and sustainable development. It ends with tools on legislative and policy reforms to make sure that the gains of CPEC are not attained at the expense of legal sovereignty of Pakistan, environment and social justice.